PENGELOLAAN ZAKAT DI LEMBAGA UPIZ PONDOK PESANTREN AL-MASHDUQIAH - Siti Aisyah; Siti Mutmainnah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
The management of zakat at the UPIZ institution (Infaq and Zakat Collection Unit) acts as a collector and distributor of ZIS from donors to mustahiq, with the principle of being trustworthy and professional with the aim of providing maximum benefits to the outside community and students who are in the Al-Mashduqiah Islamic boarding school. This type of research uses descriptive qualitative, the aim is to find out the management practices carried out by the UPIZ institution from donors to mustahiq. The data collection technique carried out by the researcher was through interviews between researchers and UPIZ institutional donors. The results of the research obtained from the interviews are the development of the UPIZ institution which has very singular (special) principles and objectives from its neatly arranged management and management system, which can create prosperity for the community itself or for the students in the Islamic boarding school area.